Models and Methods of Secure Routing in IoT - Егбе Годсон Агбара (My University, 2020)
The purpose of the work is the analysis of models, methods, and protocols of secure routing in IoT in order to increase network security. Research methods are analytical modeling, simulation, formalization, and comparison. With the rapid growth in technology and the importance of data, we are heading into a world where everything and everyone will be connected and IoT will be the underlying technology that makes this possible. While the core to the functionality of IoT is its routing and the way low-powered sensory devices or nodes self-organize and share information either data packets information or routes in between themselves. The analysis of IoT architectures, routing-related issues, and challenges in IoT, as well as the current state of secure routing protocols in IoT, was carried out in the work. Particular attention is paid to the model of secure routing in IoT and its investigation. The modeling IoT routing protocols with the MATLAB environment was also presented. A mathematical model of secure routing in IoT and a numerical study on a fragment of a wireless sensor network were presented.
Моделі та методи безпечної маршрутизації в IoT
Keywords: secure routing; IoT; trust based protocols